Two distinct antigen systems in human B lymphocytes: identification of cell surface and intracellular antigens using monoclonal antibodies. - Ishii, Y (1984)
Two distinct antigen systems (L26 and L27) specifically expressed in human B lymphocytes were identified using TB2-2B3 (2B3) and T3-5B3 (5B3) monoclonal antibodies, respectively. Whereas L26 antigen defined by 2B3 were rarely expressed on the surface of B cells but abundant in the cytoplasm, 127 antigens detected by 5B3 was clearly expressed on the cell surface. These two antigens appeared to be restricted in their expression to B cells, as they were found in most B cells but not other cell types including thymocytes, T cells, monocytes and granulocytes. Functional studies demonstrated that L27 was more easily lost from B cells after activation with pokeweed mitogen than was L26. Likewise, plasma cell myeloma, as well as normal plasma cells, was devoid of both L26 and L27, whereas immunoblastic sarcoma of B cell type expressed L26 but not L27. These two antigens co-existed in the same B cell lines including Epstein-Barr virus transformed B cell lines, B cell type acute lymphatic leukaemia (B-ALL) cell line, Burkitt's lymphoma cell lines and myeloma cell lines, but pre-B and common ALL cell lines were entirely negative for both L26 and L27. Immunoprecipitation studies showed that L26 consisted of at least two polypeptide chains with molecular weights of 30K and 33K daltons, which were clearly distinct from HLA-DR antigens. The antigen L27 is presently under study.